Deep RNA sequencing of muscle tissue reveals absence of viral signatures in dermatomyositis - Corman, Victor M.; Preusse, Corinna; Melchert, Julia; Benveniste, Olivier; Koll, Randi; Goebel, Hans-Hilmar; Jones, Terry C.; Drosten, Christian; Schara-Schmidt, Ulrike; Leonard-Louis, Sarah; et al. (Free Neuropathology, 2024)
Objective: To explore a possible connection between active viral infections and manifestation of Dermatomyositis (DM). Methods: Skeletal muscle biopsies were analyzed from patients diagnosed with juvenile (n=10) and adult (n=12) DM. Adult DM patients harbored autoantibodies against either TIF-1γ (n=7) or MDA5 (n=5). Additionally, we investigated skeletal muscle biopsies from non-diseased controls (NDC, n=5). We used an unbiased high-throughput sequencing (HTS) approach to detect viral sequences. To further increase sequencing depth, a host depletion approach was applied. Results: In this observational study, no relevant viral sequences were detected either by native sequencing or after host depletion. The absence of detectable viral sequences makes an active viral infection of the muscle tissue unlikely to be the cause of DM in our cohorts. Discussion: Type I interferons (IFN) play a major role in the pathogenesis of both juvenile and adult dermatomyositis (DM). The IFN response is remarkably conserved between DM subtypes classified by specific autoantibodies. Certain acute viral infections are accompanied by a prominent type I IFN response involving similar downstream mechanisms as in DM. Aiming to elucidate the pathogenesis of DM in skeletal muscle tissue, we used an untargeted high-throughput sequencing and a host depletion approach to detect possible causative viruses.